Estimation of the fracture toughness threshold of a ferritic steel at the lower ductile to brittle transition region - Berejnoi, Carlos (2016)
The ADN420 ferritic steel (A615 steel Grade 60 [420]), used as reinforcing bars (rebar) in concrete, shows the so called ductile to brittle transition. Room temperature is located on the lower third region of the transition zone. In this work, the fracture toughness of this steel working at room temperature was studied statistically. For such a purpose, 125 compact test specimens were machined from commercial bars and tested at room temperature to determine the Jc and KJc critical fracture toughness values. Several continuous probability functions with threshold parameter were adjusted to the J and K datasets.